A new class of cyclin dependent kinase in chlamydomonas is required for coupling cell size to cell division - Li, Y.; Liu, D.; López-Paz, C.; Olson, Bradley J.; Umen, J. G. (My University, 2016)
Proliferating cells actively control their size by mechanisms that are poorly understood. The unicellular green alga Chlamydomonas reinhardtii divides by multiple fission, wherein a ‘counting’ mechanism couples mother cell-size to cell division number allowing production of uniform-sized daughters. We identified a sizer protein, CDKG1, that acts through the retinoblastoma (RB) tumor suppressor pathway as a D-cyclin-dependent RB kinase to regulate mitotic counting. Loss of CDKG1 leads to fewer mitotic divisions and large daughters, while mis-expression of CDKG1 causes supernumerous mitotic divisions and small daughters. The concentration of nuclear-localized CDKG1 in pre-mitotic cells is set by mother cell size, and its progressive dilution and degradation with each round of cell division may provide a link between mother cell-size and mitotic division number. Cell-size-dependent accumulation of limiting cell cycle regulators such as CDKG1 is a potentially general mechanism for size control. © Li et al.
Citation: Li, Y., Liu, D., López-Paz, C., Olson, B. J. S. C., & Umen, J. G. (2016). A new class of cyclin dependent kinase in chlamydomonas is required for coupling cell size to cell division. eLife, 5(MARCH2016). doi:10.7554/eLife.10767